Three new enchytraeid species (Enchytraeidae, Annelida) from mountain soils of Korea and ten species new for the country - Felföldi, Tamás; Dózsa-Farkas, Klára; Nagy, Hajnalka; Hong, Yong (Zootaxa, 2020)
In this paper, three new enchytraeid species (Enchytraeidae, Clitellata) are described from different mountains of Korea: Cognettia koreana sp. n., Henlea bidiverticulata sp. n. and Mesenchytraeus longidiverticulatus sp. n. Validity of these new species was confirmed by comparative morphological and molecular taxonomic analyses (based on ITS, CO1 and H3 sequences). In addition, ten enchytraeid species never recorded before from Korea were found in the studied soil samples: Bryodrilus diverticulatus Černosvitov, 1929, Cernosvitoviella atrata Bretscher, 1903, Cernosvitoviella minor Dózsa-Farkas, 1990, Cognettia lapponica Nurminen, 1965, Cognettia varisetosa (Martinsson, Rota & Erséus, 2015), Fridericia cf. sohlenii Rota, Healy & Erséus, 1998, Henlea nasuta Eisen, 1878, Marionina clavata Nielsen & Christensen, 1961, Marionina communis Nielsen & Christensen, 1959, Marionina seminuda Xie & Rota, 2001. Morphological observations and new reference DNA sequences are also provided for the above-mentioned species.